TranslatiOnal Registry for CardiomyopatHies (TORCH): rationale and first results - Seyler, Claudia; Meder, Benjamin; Weis, Tanja; Katus, Hugo; Dösch, Andreas (ESC heart failure, 2017)
Aims: Non-ischemic cardiomyopathies (CMPs) comprise heart muscle disorders of different causes with high variability in disease phenotypes and clinical progression. The lack of national structures for the efficient recruitment, clinical and molecular classification, and follow-up of patients with non-ischemic CMPs limit the thorough analysis of disease mechanisms and the evaluation of novel diagnostic and therapeutic strategies. This paper describes a national, prospective, multicenter registry for patients with non-ischemic CMPs. The main objective of this registry is to create a central hub for clinical outcome studies, a joint resource for diagnostic and therapeutic trials, a common biomaterial bank, and a resource for detailed molecular analyses utilizing patients' biomaterials. Methods and results: A comprehensive characterization of the register population and patients' subgroups is planned. First analyses will include descriptive methods evaluating the distribution of outcome variables and possible risk factors followed by test statistics in a cross-sectional design. The aim of the current study is to recruit 2300 patients all over Germany. Eligible participants are patients with primary non-ischemic cardiomyopathies, including hereditary and inflammatory dilated CMP (DCM), left-ventricular noncompaction CMP (LVNC), hypertrophic CMP (HCM), arrhythmogenic right-ventricular CMP (ARVC), myocarditis, and amyloidosis. Of already recruited patients 70% are male and 30% female. With 56% of patients included, DCM is most common. Conclusion/Outcome: The primary outcome is all-cause death. Key secondary endpoints are cardiovascular death, adequate ICD shock, survived sudden cardiac death, syncope, documented potentially life-threatening arrhythmia, cardiac transplantation, hospitalization due to worsening of heart failure (HF), and any non-elective cardiovascular hospitalization.